The Genetic and Clinical Outcomes in Fetuses With Isolated Fetal Growth Restriction: A Chinese Single-Center Retrospective Study - Zhou, Hang; Cheng, Ken; Li, Yingsi; Fu, Fang; Li, Ru; Zhang, Yongling; Yang, Xin; Jing, Xiangyi; Li, Fucheng; Han, Jin; Pan, Min; Zhen, Li; et al. (Frontiers in Genetics, 2022)
OBJECTIVE: To evaluate the utility of chromosomal microarray (CMA) in fetuses with isolated fetal growth restriction (FGR) and explore risk factors for the prediction of chromosomal aberration and perinatal adverse outcomes. METHOD: This study has included 271 fetuses of estimated fetal weight less than the 3rd percentile without other structural malformation. Early-onset and late-onset FGR were defined as gestational weeks less than 32 weeks and more than 32 weeks respectively. These cases were performed quantitative fluorescent polymerase chain reaction (QF-PCR) and chromosomal microarray (CMA) as the first-line genetic detection strategy. Chromosomal anomalies were compared after stratified analysis by the early-onset and the late-onset FGR, ultrasound soft markers, and amniotic fluid et al. The follow-up time was within one year after birth. Logistic regression was used to seek risk predictors of chromosomal aberration and perinatal adverse outcomes for isolated FGR. RESULTS: The CMA identified clinical significant variants in 18/271 (6.6%) fetuses, and variants of unknown significance (VOUS) in 15/271 (5.5%) fetuses. Stratified analysis showed that there was a higher incidence of clinical significant variants in fetuses with the early-onset FGR compared with the late-onset (8.7%, 17/195 vs 1.3%, 1/76, P<0.05). Regression analysis showed the early gestational age (GA) at diagnosis of FGR was the major risk factor for chromosomal aberration (OR=0.846). By variable regression analysis, the early GA at and decreased estimated fetal weight (EFW) percentile of suspicion of FGR, asymmetrical FGR, abnormal amniotic fluid, and severe preeclampsia all could increase the risk of the adverse outcomes of isolated FGR including, intra-uterine fetal death (IUFD), termination of pregnancy (TOP) and preterm birth in pregnancies of FGR. CONCLUSION: This study emphasized the value of microarray for unbalanced genomic variants in fetuses with isolated FGR, especially since the gestational age of nullipara was less than 32 weeks. Perinatal adverse outcomes of isolated FGR were influenced by multiple factors including GA and estimated fetal weight (EFW) percentile of suspicion of FGR, asymmetrical FGR, abnormal amniotic fluid, and severe preeclampsia.